Ethnicité, Nourriture et Politique L’exemple des Yasa de la Côte Sud du Cameroun - Ndonko, Flavien Tiokou (Afrika Focus, 1993)
In Cameroon, ethnicity is present in food as well as in anthroponymy. Neighbou- ring populations use it to auto-identify themselves and to indicate their spatial settlement. The ’leaves’eaters’, the ’crabs’eaters’ and the ’"fruits de l’arbre à pain"-eaters’ live together in peace on the Coast of the country by assuming their ethnicity. They even take over new political and administrative structures as guide mark in self presentation. Even the political power who officially tries to ’erase’ ethnicity is not able to compose without it. Ethnicity has become a political strategy and is being mobilized or demobilized to balance or control the power. KEY WORDS: Ethnicity, food, politics, space, stereotype